Two Sculptured Stones recently found in Orkney - Marwick, Hugh (Proceedings of the Society of Antiquaries of Scotland, 1924)
A sculptured stone was found in the vicinity of a broch at Chapel Knowe. It has a very delicately incised human figure wearing a gown or cloak reaching below the knees, depicted in profile looking towards the left. A symbol stone from Greens, St Andrew's was discovered during drain digging. The symbols include a mirror, crescent and V-shaped rod.